Analisis Penerapan Pendidikan Karakter pada Pembelajaran di SD YPK Ermasu - My Ismail; Eva Nirtha; Rudolfus Ruma Bay (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the implementation of character education in learning at SD YPK Ermasu. This study aims to analyze the application of character education in learning at SD YPK Ermasu. 2Character education plays an important role in shaping the personality of quality students, by instilling moral, social, and emotional values that support the self-development of students. The method used in this study is qualitative descriptive with a case study approach, which involves observation, interviews, and documentation as data collection techniques. The results of the study show that the implementation of character education at SD YPK Ermasu is carried out through various learning activities, both integrated in subjects and through extracurricular activities. In addition, teachers as learning agents, play an active role in instilling character values such as discipline, responsibility, cooperation, and respect for others. Obstacles faced in the implementation of character education include the lack of supporting resources and challenges in aligning students' character with the development of the times. Nevertheless, the school continues to strive to develop the character education program optimally through teacher training and continuous evaluation. This research is expected to contribute to the development of character education in elementary schools as part of efforts to form a generation with integrity and morality.